Drilling Fluid Study: Evaluating the Quantitative Determination Method of Partially-Hydrolyzed Polyacrylamide (PHPA) Polymer in Drilling Fluid - MOHD RAZMI ZIQRI BIN AHMAD SHUKRI, MOHD (Universiti Teknologi Petronas, 2012)
This dissertation is purposed to record all the data gathered throughout author‟s study and research for this project. A deep study of Partially Hydrolyzed Polyacrylamide (PHPA) polymer is conducted and author had selected HyPR-CAP PHPA and Polymer Test Kit to be used in this project. The need for a reliable, quantitative analytical method for the determination of the PHPA polymer content of drilling mud and other water-base fluids has been evident for some time. PHPA is a short-chain polymer which is special from other type of polymer that is used in the mud system either to control wellbore shales or to extend bentonite clay in a low-solids mud. By using Polymer Test Kit – Clapper Type provided by OFI Testing Equipment, Inc (OFITE), this project is run to evaluate the quantitative determination of PHPA in mud system. This kit is supplemented with a cross reference table which is only capable to cross reference the test result to the maximum of 1 g HyPR-CAP. In the HyPR-DRILL field trial, 3 g HyPR-CAP has often been recommended. This has driven the need to expand the cross reference table to 3 g HyPR-CAP. This test determines the polymer concentration in mud systems and also involves measurement of the rate of ammonia generation while the mud filtrate is heated in the presence of sodium hydroxide solution. The ammonia is removed from the reaction vessel with a slow air purge and detected with a Dräger-Tube™. The approximate concentration of polymer is determined by measuring the time required for the Dräger-Tube™ to turn blue. The time for the Dräger-Tube™ to turn blue are taken and compare them to the reference table given by OFITE as we can know the concentration of PHPA polymer in our mud systems. Author managed to evaluate the quantitative determination for HyPR-CAP using Polymer Test Kit but not managed to expand the cross reference. Besides the results are not repeatable and reliable, this method also has lot of interferences as stated in the discussion part.